Hubungan Antara Problem Focused Coping dan Emotion Focused Coping dengan Homesick pada Mahasiswa Rantau - Barus, Elia Malem Ateta; Mandang, Jofie Hilda; Kumaat, Theophany Deasinatalia; Febrianto, Rachman (Universitas Muhammadiyah Metro, 2024)
The study aims to determine whether there is a relationship between problem-focused coping and emotion-focused coping with homesickness in regional students in North Sulawesi. The population in this study is 4th-semester Psychology students studying at Manado State University, Manado State Christian Institute, and Manado State Islamic Institute. The results of the Pearson Correlation Test between the variables Problem-Focused Coping and Homesick was -.702. The interpretation of the results of this correlation is strongly correlated, and the form of the relationship is negative. The Pearson Correlation Test result of the Emotion-Focused Coping with Homesickness variable was -.732. The interpretation of the results of this correlation is strongly correlated, and the form of the relationship is negative. To measure the closeness of the three variables, a multiple correlation test was used between the variables problem-focused coping and emotion-focused coping with homesickness. The results obtained were jointly correlated and negatively influential—the result of Sig. F Change is 0.000, which is 0.000<0.05. The result of the R-value is 0.845. It was concluded that the degree of relationship between the three variables was perfectly correlated.